Access Rights Policy and Population Data Utilization: Evidence from the Population and Civil Registration Office of Depok City, West Java Province - Zefanya Yosua Jocom; Ismail Nurdin; Suhajar Diantoro; Faria Ruhana (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: NIK-based population data access rights implementation is one of the challenges of strategic governance in Indonesia's digital transformation agenda. Permendagri No. 17 of 2023 has declared that such structured data-sharing is implemented through Cooperation Agreements (PKS), but empirical study on how Disdukcapil at the regional level navigates the gap between regulatory mandates and operational realities remains elusive. Objective: This study aims to examine the implementation of population data access rights using NIK-based policy at Depok City Disdukcapil, along with its challenges and management strategies. Methods: A descriptive qualitative approach with a constructivist paradigm was used, which included interviews, field observations, and literature review, followed by data reduction, triangulation, and presentation of the information obtained using NVivo 11 Plus. Results: The findings reveal that the optimization of population data utilization across various public service sectors remains uneven. Furthermore, there is a declining trend in the implementation of data access rights and a lack of understanding regarding the access mechanisms. Despite these issues, the policy implementation operates through structured digital governance, regulation-based frameworks, and cross-institutional collaboration, which enhances service effectiveness, time efficiency, data accuracy, and the precision of government programs. However, obstacles such as limited human resources, infrastructure constraints, inter-agency (OPD) coordination gaps, and technical and regulatory challenges persist. As a result of this study, the researcher formulates the ANYA-COCO (Affected, Negotiated, Yield, Authority – Collaborative-Controlled) model as a framework for policy implementation. This model aims to strengthen adaptive digital governance, data literacy, cross-agency coordination, and performance-based monitoring to ensure that population data utilization access becomes more effective and efficient. Conclusion: Adaptive digital governance, improvement of data literacy, coordination and synchronization across government agencies based on three levels, and monitoring based on performance indicators are recommended to ensure that NIK-based population data access utilization can be more responsive, safe, and sustainable. This research offers practical policy recommendations that can be replicated across similar Disdukcapil offices in the country.